The characterization of antimicrobial resistance and virulence in Coagulase-Negative Staphylococci isolated from neonatal blood cultures in the Western Cape - Cloete, Stephanie Simone (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.